2013
DOI: 10.1007/s12010-013-0362-4
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Pressure Plasma Pretreatment of Sugarcane Bagasse: The Influence of Moisture in the Ozonation Process

Abstract: Sugarcane bagasse samples were pretreated with ozone via atmospheric O2 pressure plasma. A delignification efficiency of approximately 80 % was observed within 6 h of treatment. Some hemicelluloses were removed, and the cellulose was not affected by ozonolysis. The quantity of moisture in the bagasse had a large influence on delignification and saccharification after ozonation pretreatment of the bagasse, where 50 % moisture content was found to be best for delignification (65 % of the cellulose was converted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 24 publications
0
16
0
1
Order By: Relevance
“…In the present calculations, we have used as biomass representative, sugarcane bagasse (Figure ). The raw sugarcane bagasse was characterized employing the procedure described in ref . The chemical analysis revealed that the biomass is composed of (38.50 ± 0.20)% of lignin, (20.60 ± 0.30)% of hemicellulose, (36.90 ± 0.50)% of cellulose, and (2.00 ± 0.10)% of ash.…”
Section: Model Descriptionmentioning
confidence: 99%
“…In the present calculations, we have used as biomass representative, sugarcane bagasse (Figure ). The raw sugarcane bagasse was characterized employing the procedure described in ref . The chemical analysis revealed that the biomass is composed of (38.50 ± 0.20)% of lignin, (20.60 ± 0.30)% of hemicellulose, (36.90 ± 0.50)% of cellulose, and (2.00 ± 0.10)% of ash.…”
Section: Model Descriptionmentioning
confidence: 99%
“…In this sense, the research to obtain more effective ozonizers could enable economically viable processes. Ozone interaction mechanism with the biomass is relatively well known (Souza-Corrêa et al 2013b), but more research is needed to unravel the influence and the role of other radicals (e.g. singlet states of atomic and molecular oxygen, OH, H 2 O 2 ) in biomass degradation processes.…”
Section: Biomass Processing and Biofuels Productionmentioning
confidence: 99%
“…Fourier transform infrared spectroscopy (FTIR) was employed to analyze the lignin bond disruptions and morphology changes of the bagasse surface that occurred due to the ozonolysis reactions as well. Appropriate chemical characterization of the lignin content in bagasse before and after its ozonation was also carried out and the reader interested can see in this paper for more details (Souza-Corrêa et al 2013b. Sugarcane bagasse samples pretreated with ozone in a downstream of an atmospheric-pressure O 2 DBD plasma showed delignification efficiency of approximately 80 % in 6 h of treatment.…”
Section: Biomass Processing and Biofuels Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, the optimal water content for agricultural residues is higher than that observed for woods, due to their capacity to bond water. Souza-Correa et al (2013a) studied 10%, 25%, 50% and 75% (w/w) moisture content for ozonization of sugarcane bagasse, and found the optimum result at 50% moisture content. , working with sugarcane bagasse in a fixed bed reactor, achieved a 46% of glucose yield at 80% (w/w) moisture content, six percentage points more than at 40% (w/w) moisture content.…”
Section: Effect Of Moisture Contentmentioning
confidence: 99%